USING SUGGESTOPEDIA METHOD IN READING COMPREHENSION - Astuti, Nina Sri; Syatriana, Eny; Jumiaty, Andi Asri (FKIP Unismuh Makassar, 2024)
This research aimed to know whether Suggestopedia as Method can improve students reading comprehension especially at literal comprehension (main idea) and interpretative comprehension (conclusion) in the Second Grade Students of Madrasah Aliyah Guppi Samata. The researcher applied Pre-Experimental method with use one group pre-test and post-test design and collected data by giving pre-test and post-test. The sample for this research was Class XI of Madrasah Aliyah Guppi Samata that consisted of 15 students. The sample was taken by using Purposive Sampling Technique. The researcher wanted to know the students’ ability in reading comprehension so that, the researcher found that too much students when pre-test got poor score. The improvement of the students’ literal comprehension by using Suggestopedia Method at Second Grade of Madrasah Aliyah Guppi Samata was good. Suggestopedia method brings good effect in reading comprehension because with using Suggestopedia, the students be active, relax, and not afraid in the class, the students’ can improve reading skill, and can help students to stimulate good mental condition. Meanwhile, the improvement of the students’ interpretative comprehension by using Suggestopedia Method at Second Grade of Madrasah Aliyah Guppi Samata was good. The effect of suggestopedia method in reading comprehension in term of interpretative comprehension help students to stimulate students’ good mental condition before the students’ answer the questions.